الوظائف التنفذية الكف و المرونة عند الطفل المعاق سمعيال حامل السمع القوقعي - بن عيسى وداد; بن يحي مداني (My University, 2023)
This study aimed to reveal the relationship between hearing disability and executive functions (palm and flexibility) among hearing-impaired children carrying cochlear implants, the study adopted the descriptive approach, and the study population consisted of all hearing-impaired children carrying cochlear implants in Algeria, and the study sample reached 4 cases of students of the fourth and fifth year of primary school, and it was based on observation and the application of the Strom test as research tools, the results of the study showed a fairly average relationship between hearing disability and executive functions ( The results also showed that most hearing-impaired children with cochlear implants suffer from difficulties in palm and flexibility, as they have difficulty in concentrating and paying attention, following up on details, changing plans, and facing challenges. Keywords: executive functions, palm, flexibility, hearing impairment, cochlear implants.